Rehabilitation And Execution Of The Death Penalty In Narcotics Offenses - Tarmizi Tarmizi; Sintong Marbun (International Asia Of Law and Money Laundering (IAML), 2022)
Drug abuse, namely drugs, is a threat to the sovereignty of the nation and the state of drug eradication requires the role of all parties to narrow the movement of drug dealers who are still trying to market these illegal goods in indonesia. The regulation on narcotics crime and death penalty is very important in regulating the law for perpetrators of narcotics crime for the benefit of the sovereignty of the nation and state.In Indonesia today, the imposition of criminal sanctions in the form of capital punishment by a judge for perpetrators of narcotics is one of the policies adopted in Law No. 35 of 2009 on narcotics and cannot be separated from the criminal law norms adopted by criminal law so far, for example in Article 10 of the Criminal Code. Another thing in other parts of the world there is a significant development of narcotics users by taking depenalization actions against users aimed at replacing prison sanctions which are sometimes applied other criminal sanctions such as Social Work sanctions. The research method used is empirical juridical meaning is to identify and conceptualize the law as a real and functional social institution in a patterned life system. Meaning is to identify and conceptualize the law as a real and functional social institution in a patterned living system.